2019
DOI: 10.1371/journal.pone.0216359
|View full text |Cite
|
Sign up to set email alerts
|

Plasma protein thiolation index (PTI) as a potential biomarker for left ventricular hypertrophy in humans

Abstract: Background Left ventricular hypertrophy (LVH) has been associated with oxidative stress, although not with the protein thiolation index (PTI). This study explored the potential use of PTI as a biomarker of oxidative stress in patients with LVH. Methods We recruited 70 consecutive patients (n = 35 LVH and n = 35 non-LVH) based on an echocardiography study in our institution (left ventricular mass indexed to body surface area). Plasma levels of both S-thiolated protein an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 47 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…Recently, our group has shown that PTI could be a new biomarker of oxidative stress in patients with LVH: PTI was higher in patients with LVH compared with patients without LVH, the area under the receiver operating characteristic curve was 0.75, sensitivity was 70.6%, and specificity was 68.6%. Thus, PTI could be used to screen for LVH (Quintana-Villamandos et al, 2019). In the present study, we have observed the same result, the SHR control group showed a markedly higher PTI than the WKY control group.…”
Section: Effects Of Dronedarone On Thiol-specific Oxidative Stresssupporting
confidence: 85%
See 1 more Smart Citation
“…Recently, our group has shown that PTI could be a new biomarker of oxidative stress in patients with LVH: PTI was higher in patients with LVH compared with patients without LVH, the area under the receiver operating characteristic curve was 0.75, sensitivity was 70.6%, and specificity was 68.6%. Thus, PTI could be used to screen for LVH (Quintana-Villamandos et al, 2019). In the present study, we have observed the same result, the SHR control group showed a markedly higher PTI than the WKY control group.…”
Section: Effects Of Dronedarone On Thiol-specific Oxidative Stresssupporting
confidence: 85%
“…On the other hand, an enhanced oxidative stress status may be related to the induction or maintenance of cardiac remodeling by its action on these signaling pathways ( Maulik and Kumar, 2012 ; Sag et al, 2014 ; Moris et al, 2017 ). Recently, our group has demonstrated that patients with LVH show increased levels of protein thiolation index (PTI; Quintana-Villamandos et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group investigated PTI, a biomarker of oxidative stress that combines oxidative damage (S-thiolated proteins) and antioxidant capacity (thiols) in plasma from patients with LVH. 16 PTI showed an AUC of 0.75, with sensitivity of 70.6% and specificity of 68.8%, thus suggesting that it could be used to screen for LVH. 16 The OXY-SCORE (combining several biomarkers of oxidative damage and antioxidant capacity) shows similar AUC values (0.74) and diagnostic validity indexes; however, it exhibits a limited variability, and precision and completeness are expected to increase with the number of parameters included.…”
Section: Discussionmentioning
confidence: 98%
“…11 In addition, the global index of plasma oxidative stress was shown to be a therapeutic target in coronary artery remodeling in a model animal with primary hypertension. 13 Therefore, the global index Reproduced with permission from Quintana-Villamandos et al 16 The data are expressed as the mean ± SEM, frequency (percentage). * p < 0.001.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation